PENGARUH LITERASI KEUANGAN DAN INFORMASI AKUNTANSI TERHADAP MINAT MENGGUNAKAN PEER TO PEER LENDING SYARIAH PADA MAHASISWA TATA NIAGA - Tillah, Atia; Amin, Haris Al; Halim, Abdul (Politeknik Negeri Lhokseumawe, 2024)
Abstract: This research was conducted on Commerce Students at the Lhokseumawe State Polytechnic. This research aims to determine the influence of financial literacy and accounting information on interest in using sharia peer to peer lending among Commerce Students. In this research, data was collected using tools in the form of observations, interviews and questionnaires for 101 respondents using a simple random sampling technique, which aims to determine the respondents' perceptions of each variable. The type and source of data in this research is quantitative research, primary and secondary data sources. The analysis used includes data instrument tests (validity and reliability tests), multiple linear regression analysis, classical assumption tests (t test, F test, and coefficient of determination). From the research results, it can be seen that the variables of financial literacy and accounting information have a significant or positive effect simultaneously on interest in using sharia peer to peer lending. From the t test, the results showed that financial literacy had a significant effect on using sharia peer to peer lending and my information had a significant effect on interest in using sharia peer to peer lending.Keywords: Financial Literacy; Accounting Information; Sharia Peer to Peer Lending